On framework development for the dynamic prosumer coalition in a smart grid and its evaluation by analytic tools - Sumesh, Sreenithya; Krishna, Aneesh; Potdar, Vidyasagar; Nimmagadda, Shastri (2019)
Managing prosumers participation in energy trading becomes complicated, as the number of prosumers in smart grid is expected to rise. In this situation, it is safe to group active prosumers into groups or coalitions. By utilising analytical tools, like game theory, the method for grouping or coalition formation of prosumers can be carefully studied. After analysing prosumers behaviour in energy profile, we propose a novel dynamic, decentralised prosumer coalition formation method based on game theory that can satisfy utility grid demands. A conceptual framework is developed for coalition formation and energy management among prosumers in a dynamic environment. This approach has the potential to increase the size and number of coalitions without a central controller to better manage renewable energy usage and trading with energy buyers. We validate the performance of adopting a game theoretic approach, assessing the strategy using open and shared data sources.